Visible Meridian Phenomena after Acupuncture: A Series of Case Reports - Nikolay Dimitrov; Nikola Tomov; Dimitrinka Atanasova; Stiliyan Iliev; Tatyana Tomova; Dimitar Sivrev; Zoya Goranova (Journal of Acupuncture & Meridian Studies, 2021)
Background : In accordance with the meridian theory of Traditional Chinese Medicine (TCM), meridian phenomena are observed along the course of a meridian following acupuncture. Their visible manifestations include alterations in the color (reddening or whitening) of the skin as well as papule and vesicle formation. Objectives: The aim of the present work is to report a series of visible meridian phenomena manifested in human subjects and to correlate them to TCM concepts. A total of 1,200 patients, on whom classical acupuncture (with standard single-use needles without electrostimulation or moxibustion) was applied, were carefully observed and documented. Methods : Visible meridian phenomena were photographed using standard photographical equipment and compared to classical acupuncture channels used by TCM. Results : Ten patients (5 male, 5 female) exhibited visible meridian phenomena. Lines, concurring with the meridians, were observed: white lines in seven cases and red lines in three cases. The duration of the two kinds of phenomena was different. White lines remained visible for a shorter period (10-15 min), whereas red lines were seen for up to one hour after needle removal. Conclusion : These observations indicate that visible meridian phenomena following acupuncture are objective, albeit rare, findings that coincide with the acupuncture channels described in the classical works of TCM. The presence of such phenomena provides a new insight into the concept of meridians and explains the development of the idea in its historical context.